Nitroprusside inhibits calcium‐induced impairment of red blood cell deformability. Issue 2 (19th June 2013) - Barodka, Viachaslau; Mohanty, Joy G.; Mustafa, Asif K.; Santhanam, Lakshmi; Nyhan, Aoibhinn; Bhunia, Anil K.; Sikka, Gautam; Nyhan, Daniel; Berkowitz, Dan E.; Rifkind, Joseph M.
<x xml:space="preserve">Abstract</x> Background Red blood cell (RBC) deformation is critical for microvascular perfusion and oxygen delivery to tissues. Abnormalities in RBC deformability have been observed in aging, sickle cell disease, diabetes, and preeclampsia. Although nitric oxide (NO) prevents decreases in RBC deformability, the underlying mechanism is unknown. Study Design and Methods As an experimental model, we used ionophore A23187–mediated calcium influx in RBCs to reduce their deformability and investigated the role of NO donor sodium nitroprusside (SNP) and KCa3.1 (Gardos) channel blockers on RBC deformability (measured as elongation index [EI] by microfluidic ektacytometry). RBC intracellular Ca2+ and extracellular K+ were measured by inductively coupled plasma mass spectrometry and potassium ion selective electrode, respectively. Results SNP treatment of RBCs blocked the Ca2+ (approx. 10 μmol/L)‐induced decrease in RBC deformability (EI 0.34 ± 0.02 vs. 0.09 ± 0.01, control vs. Ca2+ loaded, p < 0.001; and EI 0.37 ± 0.02 vs. 0.30 ± 0.01, SNP vs. SNP plus Ca2+ loaded) as well as Ca2+ influx and K+ efflux. The SNP effect was similar to that observed after pharmacologic blockade of the KCa3.1 channel (with charybdotoxin or extracellular medium containing isotonic K+ concentration). In RBCs from KCa3.1–/– mice, 10 μmol/L Ca2+ loading did not decrease cellular deformability. A preliminary attempt to address the molecular mechanism of SNP protection suggests the involvement of cell surface thiols. Conclusion Our results suggest that nitroprusside treatment of RBCs may protect them from intracellular calcium increase–mediated stiffness, which may occur during microvascular perfusion in diseased states, as well as during RBC storage.